Nauki humanistyczno-społeczne stymulatorem zrównoważonego rozwoju społeczeństwa, czyli statystyka punktów i cytowań vs społeczna odpowiedzialność uczelni = The humanities and social sciences as a stimulus for a sustainable development of society: publication points and citation statistics versus social responsibility of universities - Kędzierska, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Education has been and remains the strongest stimulus for social development, and its goal has always been to prepare young people for effective and responsible social and professional activity in various stages of life. The role of universities and other tertiary education insitutions is strategic in this respect. By working with young people in the final stage of formal education, these institutions should prepare them for supporting a sustainable development of society through a responsible and competent fulfillment of social and professional roles. A permanent reference to the needs and problems of the changing society, should be, in addition to a high level of academic teaching as well as research and teaching activity, a priority for university.
Keywords: edukacja i nauka dla zrównoważonego społeczeństwa; społeczna odpowiedzialność uczelni wyższych; rola i funkcje systemu edukacji w społeczeństwie; research and education for sustainable development of society; university social responsibility; role and functions of the education system in society